Vasoactive-inotropic Score for Early Detection and Mortality Prediction of Sepsis in Children - Aileen Clarissa Dauhan; Aridamuriany Dwiputri Lubis; Munar Lubis (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Early detection and treatment of sepsis can prevent septic shock and reduce mortality rate. Troponin can become a prognostic factor in sepsis. However, not all health facilities are equipped to assess troponin levels. Vasoactive-inotropic score (VIS) is a simpler and more accessible method to describe hemodynamic status. The aim of this study was to assess the suitability of VIS score as early prognosis and mortality predictor of sepsisMETHODS: A retrospective study was conducted to determine the correlation between VIS and troponin levels for sepsis cases in Pediatric Intensive Care Unity (PICU) Haji Adam Malik Hospital, Medan from January 2018 to December 2019. VIS score at 48 hours, maximum VIS score, pediatric logistic organ dysfunction-2 (PELOD-2) score, cardiac troponin levels at 48 hours were taken from medical records.RESULTS: There were 54 samples analyzed. VIS scores were positively correlated (p<0.001) to troponin T and troponin I levels at 48 hours (r=0.670 and r=0.606, respectively). VIS at 48 hours and maximum VIS were related to mortality (p=0.001 and p<0.001, respectively). VIS score at 48 hours could be used as a predictive factor for mortality (area under the curve (AUC): 79.7%, p<0.001) with a cut-off point at 11 (74.4% sensitivity and 80% specificity). High VIS at 48 hours indicated poor outcomes of sepsis in children with odd ratio (OR) value: 1.99 (95% confidence interval (CI): 1.25-3.19).CONCLUSION: Vasoactive-inotropic score was suitable as an alternative to cardiac troponin T and troponin I levels at 48 hours to early detect myocardial dysfunctions and mortality in children.KEYWORDS: troponin, vasoactive-inotropic score, sepsis, children, mortality